Odpowiedzi

Najlepsza Odpowiedź!
2009-12-06T17:30:10+01:00
X6-5x5=0;
x⁶ -5x⁵ = 0
x⁵( x -5 =0
x⁵ = 0 lub x-5 = 0
x= 0 lub x = 5

x5-5x-25x3=0;
x⁵ -5x -25x³ = 0
x(x⁴-5 -25x²) =0
x = o lub x⁴ -25x² -5 = 0
x =0 lub wstawiam dodatkową niewiadomą x² = t
t² -25t -5 = 0
Δ = (-25)² - 4*1*(-5) = 625 + 20 = 645
√Δ = √645
√Δ = √3*√5√43
t₁ = [-(-25) -√645] : 2*1 = (25- √645 ): 2
t² = [-(-25) +√645] : 2*1 = (25-+√645 ): 2
wracam do poprEdnich oznaczeń

x² = t₁ lub x² = t₂
x² = (25- √645 ): 2 lub x² = (25-+√645 ): 2
x = √ (25- √645 ): √2 lub x = √(25-+√645 ): √2


x+5x2=0;
x +5x² = 0
x( 1 +5x) = 0
x = 0 lub 1 +5x = 0
x =0 lub 5x = -1
x =0 lub x = -1/5

x3-8x2+16x=0
x(x² - 8x + 16) = 0
x( x - 4)² = 0
x = 0 lub (x-4)² = 0
x = 0 lub x-4 = 0
x = 0 lub x = 4 ( podwójnya pierwiatek)